Intervention program using a robot for children with Autism Spectrum Disorder (Research, Society and Development, 2021)
This study investigated the effectiveness on social skills development of an educational intervention program for schoolchildren with autism spectrum disorder (ASD) using an educational robot. Over the period of a month, four boys with ASD, ranging in age from 7 to 14 years, participated in structured educational scenarios involving the robot “Edison”, which is in the form of a toy car, with the aid of a teacher/researcher. The behavior of the four boys during the sessions was recorded by an observer, using an observation form. The boys appeared to enjoy the intervention sessions, and a positive outcome was observed following interaction with the robot. Specifically, by the end of the month of intervention, all the boys showed improvement in social skills and cooperation skills and a reduction in untoward social behaviors. They showed an increase in eye contact, followed instructions and appeared to understand the social rules better, and in general their interaction with the teacher and with each other was enhanced. In conclusion, teachers can use robots in programs aimed at improving the social and communication skills of schoolchildren with ASD.